Prevalence of thyroid stimulating hormone dysfunction among sofosbuvir‐treated HCV‐infected patients: A real‐world clinical experience. Issue 3 (17th October 2018) - Wahid, Braira; Waqar, Muhammad; Rasool, Nouman; Wasim, Muhammad; Khalid, Ifrah; Idrees, Muhammad
Abstract : Thyroid dysfunctions occur frequently among hepatitis C virus (HCV)‐infected patients. Accumulating evidence has shown the higher incidence of thyroid dysfunctions in interferon‐treated patients that was previously the standard of care therapy. However, the prevalence of thyroid disorders has not been studied in the recently developed interferon‐free regimens or direct‐acting antiviral (DAA) drugs‐treated patients. We recruited 37 patients who had just completed 6 months long sofosbuvir‐based treatment, and 26 interferon‐treated patients were also included in the study. Serum thyrotropin level of all participants was measured using VIDAS. We observed thyroid dysfunctions in both pegylated interferon–experienced and DAA drug–experienced patients but the prevalence of hyperthyroidism was found significantly higher in patients treated with interferon‐based regimen as compared with interferon‐free regimens. This high prevalence of hypothyroidism in patients with HCV posttreatment highlights the need for regular periodic screening of patients during the treatment.